Direct immunofluorescence cannot be used solely to differentiate among oral lichen planus, oral lichenoid lesion, and oral epithelial dysplasia - Nattanich Korkitpoonpol; Patnarin Kanjanabuch (Journal of Dental Sciences, 2023)
Background/purpose: Some red and white lesions may have similar manifestations, making them difficult to be diagnosed. A direct immunofluorescence (DIF) assay can assist in making a final diagnosis of oral lichen planus (OLP). The aim of this study was to evaluate and compare the DIF profile in patients who had the clinical presentations of OLP and were histopathologically diagnosed with OLP, OLL (oral lichenoid lesion), or OED (oral epithelial dysplasia). Materials and methods: The data were obtained from the medical records of 136 patients with the clinical presentations of OLP. Demographic information, histopathological diagnosis, malignant transformation, and DIF results were collected and analyzed. Results: In this study, 117 patients (86.0%) were DIF-positive, while 19 patients (14.0%) were DIF-negative. The highest DIF-positivity rate was in the OLP group (88.9%) followed by the OLL (83.7%), and the OED groups (81%). There were no significant differences in DIF-positivity rate, type of immunoreactants, location, or interpretation among these groups. Shaggy fibrinogen at the basement membrane zone (BMZ) was the most common DIF pattern in all groups. Conclusion: The DIF assay alone cannot be regarded as sufficient evidence for OLP, OLL, and OED differentiation. A histopathological examination is required to determine the presence of epithelial dysplasia or malignancy. To diagnose dysplastic lesions with the clinical manifestations of OLP, careful clinicopathologic correlation is mandatory. Due to the lack of scientific evidence to identify the primary pathology and the ongoing malignancy risk of epithelial dysplasia, meticulous long-term follow-up plays a crucial role in patient management.